2018
DOI: 10.1002/smll.201801385
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Enhancement of Fluorescence by Bimetal Mediated Surface Plasmon Coupled Emission for Highly Sensitive Quantitative Diagnosis of Double‐Stranded DNA

Abstract: Plasmonic enhancement of fluorescence from SYBR Green I conjugated with a double-stranded DNA (dsDNA) amplicon is demonstrated on polymerase chain reaction (PCR) products. Theoretical computation leads to use of the bimetallic (Au 2 nm-Ag 50 nm) surface plasmons due to larger local fields (higher quality factors) than monometallic (Ag or Au) ones at both dye excitation and emission wavelengths simultaneously, optimizing fluorescence enhancement with surface plasmon coupled emission (SPCE). Two kinds of reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
63
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 55 publications
2
63
1
1
Order By: Relevance
“…The electron oscillation originating from electromagnetic waves triggers a binding interaction event in the nanoparticle interface, thus providing high sensitivity [19]. Moreover, this plasmonic event can be tuned to excite the fluorescence dye-labeled bioprobe that exhibits ultra-sensitivity in order to detect the H5N1 virus [20,21]. Advanced bioprobes have been developed to detect H5N1 accurately with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron oscillation originating from electromagnetic waves triggers a binding interaction event in the nanoparticle interface, thus providing high sensitivity [19]. Moreover, this plasmonic event can be tuned to excite the fluorescence dye-labeled bioprobe that exhibits ultra-sensitivity in order to detect the H5N1 virus [20,21]. Advanced bioprobes have been developed to detect H5N1 accurately with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The 5′ end of DNA 3 W Jb was labeled with FAM dye (FAM/3 W Jb) for signal enhancement. It is reported that the fluorescence dye can be excited by a plasmonic field, which increases the detection sensitivity effectively [20,21]. To increase the LSPR enhancement effect, FAM dye was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient detection of fluorescence from quantum emitters (QEs), such as semiconductor quantum dots (QDs), fluorescent dyes, or J‐aggregates, is vital for optical sensing and microscopic imaging in the fields of quantum information, molecular biology, and analytical chemistry . The radiation shape of the fluorescence flowing into the far field is a critical factor for efficient photon collection.…”
Section: Introductionmentioning
confidence: 99%
“…This is then followed by a near-field coupling of the excited state of dye molecules with the surface plasmons, at an emission wavelength of (λ em ). This leads to directional radiation at λ em into a transparent high index medium interfaced with the plasmonic metal film [ 5 , 6 , 7 , 8 , 9 , 10 , 23 , 24 , 35 , 36 ]. The directional radiation would favor fluorescence collection efficiency, which also contributes to the SNR elevation.…”
Section: Introductionmentioning
confidence: 99%